2015
DOI: 10.1111/jpc.12935
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D is associated with hypertension in paediatric obesity

Abstract: Overweight and obese youth attending specialist obesity services have a high prevalence of vitamin D deficiency. In this population, lower levels of vitamin D were seen in those with greater adiposity, and independent of this, in those who had higher blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 42 publications
7
27
1
3
Order By: Relevance
“…Severe vitamin D deficiency leads to rickets with negative impact on height but the impact of moderately lowered vitamin D level in adolescents on final height remains unclear [21]. The negative relation between 25(OH)D status and BMI is consistent with results of studies by Turer [22], Kao [17], and Płudowski [16]. According to Polish guidelines, both short stature and obesity are conditions associated with risk for vitamin D deficiency and indications for assessment of vitamin D status [5].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Severe vitamin D deficiency leads to rickets with negative impact on height but the impact of moderately lowered vitamin D level in adolescents on final height remains unclear [21]. The negative relation between 25(OH)D status and BMI is consistent with results of studies by Turer [22], Kao [17], and Płudowski [16]. According to Polish guidelines, both short stature and obesity are conditions associated with risk for vitamin D deficiency and indications for assessment of vitamin D status [5].…”
Section: Discussionsupporting
confidence: 74%
“…On the other hand, in a study by Kao [6] lower vitamin D concentrations were related to both higher systolic and diastolic blood pressure in overweight and obese adolescents. Noteworthy, in contrast to our study, Kao [17] did not use ABPM, which more precisely reflects blood pressure compared to office measurements.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…50 Se ha reportado en adolescentes una asociación inversa entre las concentraciones de 25(OH)D y presión sistólica. 51 Además, hay estudios en los últimos años que muestran una posible asociación en algunas formas de cáncer, tanto en adultos como en niños. 2 Futuros estudios podrán demostrar si el manejo de la deficiencia previene alguna de estas condiciones.…”
Section: Asmaunclassified
“…50 A reverse association has been reported between 25(OH)D levels and systolic blood pressure in adolescents. 51 There are other studies that have been conducted in recent years and showed a potential association with some forms of cancer, both in adults and children.…”
Section: Asthma and Vddmentioning
confidence: 99%